Private Rental Housing in Transition Countries An Alternative to Owner Occupation? (Palgrave Macmillan UK, 2018)
This book presents an overview of private rented housing in selected new EU member states and other transition countries - a topic scarcely researched to date, as it is largely part of the informal economy, and consequently often invisible to official statistics. Part I presents the private rented sector in Western and Northern European countries, the history of private renting under socialism in Central and Eastern Europe, and thematic issues such as restitution and marginalized groups depending on privately rented housing. Part II provides a series of country case studies from the Central and East European region. Part III concludes with chapters on the possibility of utilizing the private rental sector in affordable housing provision through good practices in both old and new EU member states, and sets out to further the housing policy debate on European housing regimes. This unique edited collection will be of great value to scholars of and practitioners involved in housing policy and economics, urban development, international relations, politics, economics and sociology.